On the accessibility of financial services and income inequality: an international perspective - Fu, Yifei; Liu, Lu (Technological and Economic Development of Economy, 2023)
Income inequality has long been an important issue in development economics. Applying international data from 119 countries between 2004 and 2018, this study discusses the relationship between the accessibility of financial services and income inequality. Using the density of the bank branch network to represent the accessibility of financial services, we discover that income inequality is negatively related to the accessibility of financial services, especially in less developed countries and regions. In this nexus, the poverty ratio serves as an intermediary variable. The significance of the nexus is weaker in countries where fintech is more popularized, indicating the substitution effect between fintech and traditional banking services. Nevertheless, the substitution effect is limited, and bank branches will keep playing an important role in delivering financial services. For countries with inadequate banking services, bank branches should be increased to encourage residents to participate in the financial system, while it is no longer necessary to add a large number of branches in countries where fintech has been popularized. Faced with the trend of financial digitalization and the economic shock caused by the COVID-19 pandemic, banks should launch more online services and increase intelligent machines in the branches. By doing so, financial services are more resilient to social changes, so as to alleviate the inequality of income distribution in the long term.